The effectiveness of various teaching approaches on the performance of the volleyball game - Jaroslav Popelka; Ratko Pavlović (University of Banja Luka, Faculty of physical education and sport, 2017)
The aim of the study was to determine and verify the effectiveness of various teaching approaches on changes in the level of volleyball performance in the process of teaching volleyball to pupils in primary schools. In the experimental group was used the tactical approach and in the control group the techniques (traditional) approach in teaching of volleyball. The experimental group consisted of 26 pupils and the control group consisted same number of pupils. Both groups, representing 13 to 14 year old schoolgirls in primary school. Efficiency of the teaching approaches was evaluated based of game performance. Game performance was evaluated by the method of game performance assessment based on GPAI (Game Performance Assessment Instrument) through video record. To perform statistical evaluation Mann-Whitney U-test was used. When we evaluate the tactical component of game performance "position", we found out that the difference between groups is not statistically significant (p > 0.05). By comparison "decision-making" it was discovered that the difference, between achieved performances in groups it is statistically significant (p < 0.05) in favour of the experimental group. By comparison skills execution we found out, that the difference between both groups in "serving" is not statistically significant (p > 0.05). But by comparison of passing, setting, offensive hit and team's game performance" we found out statistically significant (p < 0.05) the difference between both groups in favour of the experimental group. The acquired data pointed to the fact that in generally the tactical teaching approach appears to be a more efficient method for acquiring game skills and tactical components of the game.